THE EFFECTIVENESS OF ROSE FLOWER (ROSA CHINENSIS JACQ) ON CANDIDA ALBICANS COLONIES IN JELLY (SABOURAUD DEXTROSE AGAR) MEDIA - Erni Dwi Widyana; Tarsikah Tarsikah; Naimah Naimah (Public Health of Indonesia)
Background: Approximately 90% of women in Indonesia have the potential to experience fluor albus. Fluor albus is mostly caused by Candida Albicans. Candida Albicans is a fungus that often causes infections on people. Herbal medicine is one alternative that can be used as a raw material for anti-fungial medication of Candida Albicans.